Listening to learn audiobooks supporting literacy - Grover, Sharon; Hannegan, Lizette D.; IG Publishing (Chicago American Library Association, 2012)
Audiobooks not only present excellent opportunities to engage the attention of young people but also advance literacy. Learn how the format can support national learning standards and literacy skills in the K-12 curricula.
How it all begins -- Why listen? -- Audiobooks and learning standards -- Audiobooks and primary school : grades K-2 -- Audiobooks and the intermediate primary school : grades 3-5 -- Audiobooks and middle school, grades 6-8 -- Audiobooks and high school, grades 9-12 -- Connecting it all : audiobooks, literacy, and instructional themes -- Technology innovation supports audiobook use -- Finding the best.
Electronic reproduction.
Keywords: Reading -- United States; Literacy -- Study and teaching -- United States; Educational technology; Audiobooks; Libraries -- Special collections -- Audiobooks; School librarian participation in curriculum planning; Children -- Books and reading; Electronic books